Online Shopping Behaviour of Slovak During the COVID-19 Pandemic (Marketing i Menedžment Innovacij)
Cities and regions worldwide, not only in Slovakia but also across the globe, have implemented various procedures to diminish the spread of the coronavirus, resulting in a profound impact on consumers' shopping behaviour. With the ongoing pandemic reshaping societal norms, it is unsurprising that consumer behaviour patterns are undergoing a significant shift towards digital platforms to accommodate evolving needs and realities. Consumers have switched from conventional shopping to online shopping because, owing to the increasing risk of coronavirus, customers want to avoid public places, thus increasing their preference for online shopping. Against this backdrop, this paper focuses on the factors influencing consumers' intentions to engage in online shopping, or e-commerce, amidst the COVID-19 crisis. Specifically, it seeks to explore the role of subjective standards and perceived usefulness in shaping consumer behavior in the online shopping domain. Drawing upon a sample of 250 Slovakian consumers and employing correlation analysis, the study reveals a positive association between internal and external subjective standards and consumers' propensity to shop online. Spearman's rank correlation coefficient was applied to verify the statistically significant relationships between the analysed factors in the hypotheses. Furthermore, the results underscore the pivotal role of the apparent helpfulness of e-commerce services in driving consumers towards online purchases, particularly during the ongoing pandemic. These insights hold considerable significance for e-commerce enterprises, offering valuable guidance in understanding and adapting to prevailing consumer behaviors. By leveraging these findings, businesses can refine their sales and marketing strategies to better align with current consumer preferences, thereby fostering greater effectiveness and competitiveness in the digital marketplace. The transition to digital commerce is, especially at the time of government measures to restrict movement and impose social distancing rules, essential for all businesses, as customers switch from brick-and-mortar stores to online shopping platforms owing to social pressure or because they find it useful. In conclusion, we discuss the research findings, identify the limitations of the study, and propose further research trajectories.